Implementation of the CIBEST Model in Measuring the Success of Implementing the Product Zakat Program at BAZNAS Jeneponto District - Andi Darmawansyah Sayuti; Sirajuddin; A Syatir Sofyan; Wira Audya Iriani (www.amertainstitute.com, 2024)
This research aims to analyze the impact of the distribution of productive zakat funds by BAZNAS Jeneponto Regency with a focus on finding out the poverty level of mustahik before and after the existence of productive zakat fund assistance from BAZNAS Jeneponto Regency using the CIBEST model. This research uses quantitative methods and the type of data used in this research is secondary data in the form of data on mustahik recipients of productive zakat fund assistance at BAZNAS Jeneponto Regency and primary data obtained through distributing questionnaires and interviews. The respondents in this study were 14 mustahik households. The data analysis method used in this research is the CIBEST model and Normality Test, Paired sample T Test and Wilcoxon Difference Test using SPSS 26 tools. The results of this research show that materially poor households previously went from 6 to 0 households. And succeeded in increasing prosperous households from 8 households to 14 households. Meanwhile, in the results of the Wilcoxon test on the worship dimension score, the sig value obtained was sig. (2-tailed) of 0.003 < 0.05, there was an increase in household spiritual values. The results of the Paired Sample T Test showed that the average income value of mustahik households was 0.000 < 0.05, so it can be concluded that there was a real difference in the income of 14 mustahik households before and after receiving productive zakat fund assistance at BAZNAS Jeneponto Regency.